Dihalooxygenation of Alkynes and Alkynols: Preparation of 2,2-Dihaloketones and gem-Dihalolactols - Chaisan, Nattawadee; Ruengsangtongkul, Sureeporn; Thongsornkleeb, Charnsak; Tummatorn, Jumreang; Ruchirawat, Somsak (Synlett, 2022)
A mild and convenient method for the synthesis of 2,2-dihaloketones and gem-dihalolactols has been developed. For the synthesis of 2,2-dihaloketones, alkynes were employed as substrates to react with halogenating agents, Cl2 or ClBr, that were generated in situ from aqueous HCl and NCS or NBS, respectively. On the other hand, gem-dihalolactols could be prepared from alkynol substrates by using the same reaction conditions. This method could be applied to a broad range of substrates to give the corresponding products in low to good yields.
Keywords: dihaloketones; dihalolactols; alkynes; alkynols; halogenation